2017
DOI: 10.1080/15548627.2017.1338556
|View full text |Cite
|
Sign up to set email alerts
|

NUPR1 maintains autolysosomal efflux by activatingSNAP25transcription in cancer cells

Abstract: In the advanced stages of cancer, autophagy is thought to promote tumor progression through its ability to mitigate various cellular stresses. However, the details of how autophagy is homeostatically regulated in such tumors are unknown. Here, we report that NUPR1 (nuclear protein 1, transcriptional regulator), a transcriptional coregulator, is aberrantly expressed in a subset of cancer cells and predicts low overall survival rates for lung cancer patients. NUPR1 regulates the late stages of autolysosome proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 66 publications
2
86
1
Order By: Relevance
“…10d-f). For example, the expression of EIF4EBP1, NUPR1 and PCK2 with reported oncogenic function involved in the AKT pathway [22][23][24][25] was down-regulated upon circFAM120A knockdown (Extended Data Fig. 10g), supporting its role in promoting cell proliferation.…”
Section: Circfam120a Promotes Cell Growth By Up-regulating Its Parentmentioning
confidence: 88%
“…10d-f). For example, the expression of EIF4EBP1, NUPR1 and PCK2 with reported oncogenic function involved in the AKT pathway [22][23][24][25] was down-regulated upon circFAM120A knockdown (Extended Data Fig. 10g), supporting its role in promoting cell proliferation.…”
Section: Circfam120a Promotes Cell Growth By Up-regulating Its Parentmentioning
confidence: 88%
“…Moreover, NUPR1 maintains autolysosomal efflux and is required for the progression of non-small cell lung cancer. (15) However, Tang et al (30) have shown that NUPR1 is activated, and mediates intestinal epithelial cells death via increasing autophagy-related gene in response to Shiga toxins toxicity. Consistent with previous reports, the present study demonstrated that quercetin induced NUPR1-dependent autophagic cell death in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…(13) NUPR1 is required for the optimal expression of metabolic stress-response genes, particularly those involved in DNA repair, cell cycle regulation, apoptosis, entosis and autophagy. (14)(15)(16) Accumulated evidence has led to the integrating hypothesis that activation of NUPR1 transactivates genes necessary for autophagosome formation, autophagosome-lysosome fusion, and cargo degradation. (17) Importantly, under stress full conditions such as chemotherapy treatment, an intricate interplay between the homeostatic NUPR1 and autophagy pathways may occur in cancer cells that will ultimately dictate their fate between cell death or survival.…”
mentioning
confidence: 99%
“…Nupr1 is emerged as an important TF in the growth and migration of human glioblastoma cells [69] and a potent regulator of autolysosomal dynamics via the induction of the SNARE proteins. Nupr1 depletion impairs autolysosomal clearance and induces cytoplasmic vacuolization, suggesting a key role in neuronal autophagy [70,71]. Ccl3 is a known activator of Jak-Stat signaling during prioninduced gliosis [43,72], and deletion of Tnfrsf1 reduces the number of amyloid plaques and cognitive deficits in AD mouse models [73].…”
Section: Discussionmentioning
confidence: 99%